Togetherness A new heritage deal for Europe - Parzinger, Hermann (European Investment Bank, 2020)
Europe's cultural heritage is a vast, multifaceted mosaic showing who we were, who we are and who we aspire to be. We are all responsible for this huge, precious and fragile legacy.The coronavirus pandemic revealed that unexpected events can suddenly change our way of life. In the future, other threats could well pose further challenges to our safety, health and environment as well as our social structures, values and ability to compete on the global markets.How can Europe fulfil its promise if we do not reinvent and redesign the very basis of the European project and come up with innovative and bold solutions for a better and more sustainable future together?We need a "New Heritage Deal for Europe", a heritage-led transformation of Europe's society, economy and environment.Prof. Dr Hermann Parzinger is an archaeologist, historian and cultural heritage expert. In 2018, he was appointed Executive President of Europa Nostra, a pan-European federation for cultural heritage that represents civil society organisations seeking to safeguard Europe's cultural and natural heritage. Since 2013, Europa Nostra has been running among its key activities the 7 Most Endangered Programme in partnership with the European Investment Bank Institute.This is the fifteenth essay in the Big Ideas series created by the European Investment Bank.